Voluntourism as cartography of self: A Deleuzian analysis of a postgraduate visit to India. (June 2018) - Bone, Jane; Bone, Kate
Volunteer tourism takes place within neoliberal globalisation and reflects inequalities of privilege and mobility. This qualitative research examined the experiences of young female voluntourists who visited Delhi as part of a trip organised by an Australian University Postgraduate Student Association. The aim was to investigate the motives and potentialities embedded in their experience through interviews and journal contributions. Conceptualisations of mapping (cartography) and territorialisation informed the analysis. We found that participants mainly engaged with the experience on a superficial level within the known territory . This reflects 'soft global citizenship' as participants were uncritical about their interactions with the host community. Voluntourist experiences have the potential to destabilise the self in a process of deterritorialisation, and we contend that this is where change occurs. We bring the philosophical theorising of Deleuze and Guattari and their notions of territorialisation and cartography to the field of tourism and argue that their geophilosophical ideas lead to fruitful insights around negotiating volunteer expectations, tribulations and potential transformations.